2008
DOI: 10.1155/2008/456298
|View full text |Cite
|
Sign up to set email alerts
|

The Factors that Induce or Overcome Freezing of Gait in Parkinson’s Disease

Abstract: Freezing of gait (FoG), a transient halt in walking, is a major mobility problem for patients with Parkinson’s disease (PD). This study examined the factors that induce FoG, and identified the cues and strategies that help overcome it through a postal survey of 130 PD patients. 72% reported FoG. The factors that commonly induced FoG were turning, fatigue, confined spaces and stressful situations, in addition to emotional factors. FoG was also ameliorated by various attentional and external cueing strategies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 45 publications
(69 reference statements)
11
135
0
2
Order By: Relevance
“…Our results indicate that similar activities are avoided by PD patients and that confidence decreases with increasing task complexity, but that situations with large numbers of people e.g., crowds, social events and public transport, are also avoided as shown in previous PD samples [18]. Previous work by our group has shown that such situations trigger freezing in a large percentage of patients [48]. Therefore, such situations may be avoided because they increase the likelihood of falling through freezing.…”
Section: Discussionsupporting
confidence: 71%
“…Our results indicate that similar activities are avoided by PD patients and that confidence decreases with increasing task complexity, but that situations with large numbers of people e.g., crowds, social events and public transport, are also avoided as shown in previous PD samples [18]. Previous work by our group has shown that such situations trigger freezing in a large percentage of patients [48]. Therefore, such situations may be avoided because they increase the likelihood of falling through freezing.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, a goal-directed deficit may concur with a separate literature that highlights a shift from internal to external control in PD (van Spaendonck, Berger, Horstink, Borm, & Cools, 1995;Brown & Marsden, 1988;Cools, van den Bercken, Horstink, van Spaendonck, & Berger, 1984). Observations that PD patients have no problem initiating actions when presented with an unambiguous external stimulus (e.g., Rahman, Griffin, Quinn, & Jahanshahi, 2008;Praamstra, Stegeman, Cools, & Horstink, 1998) suggest that if anything remains intact in PD, it is the ability to act on direct S→R associations. Difficulties with the internal generation of actions and cognitive plans as well as enhanced cue-reliance and stimulus-driven behavior are more in line with a goal-directed impairment.…”
Section: Discussionsupporting
confidence: 66%
“…FoG is elicited by specific situations or triggers: turning, gait ignition (start hesitation), approaching a destination, constrictions in visual input, e.g., doorways, and stressful, rushed situations such as hearing a knock at the door [14,15,42,51]. In more advanced PD FoG may occur in open spaces in the absence of any obvious trigger.…”
Section: External Influences On Gait In Pdmentioning
confidence: 99%